The ups and downs of jobs in Georgia: what can we learn about employment dynamics from state administrative data? - Julie L. Hotchkiss; M. Melinda Pitts; John C. Robertson (Federal Reserve Bank of Atlanta, 2003)
This paper demonstrates how state administrative data (from Georgia) can be used to decompose net employment growth in order to track establishment births, deaths, contractions, and expansions over time. Even though net employment growth can look quite similar across industries, the composition of that employment change can look quite different. The panel nature of the data allow the authors to see that overall lack of expansion and continued contraction among large establishments were the driving forces behind the weak employment growth immediately following the 2001 recession.
Keywords: 330